Cytotoxicity evaluation of root canal sealers using an in vitro experimental model with roots - Teixeira, Ligia [UNESP]; Basso, Fernanda Gonçalves; Hebling, Josimeri [UNESP]; De Souza Costa, Carlos Alberto [UNESP]; Mori, Graziela Garrido; Silva-Sousa, Yara Teresinha Corrêa; De Oliveira, Camila Fávero (FapUNIFESP (SciELO), 2017)
The aim of the present study was to evaluate the cytotoxicity of root canal sealers under conditions closely resembling a clinical reality. A primary human fibroblast cell line was seeded in 24-well acrylic plates with Dulbecco’s modified Eagle’s medium supplemented with 10% serum fetal bovine (SFB) and incubated for 24 h. Root canals from premolars were filled and individually attached to nylon devices to be stabilized in the wells with the already seeded cells. Specimens were divided into groups as follows: Control: gutta-percha cones (GPC); AH Plus+GPC; Sealapex+GPC; MTA Fillapex+GPC and Endofill+GPC. After 24 and 48 h, cell viability and morphology were evaluated by MTT assay and scanning electron microscopy (SEM), respectively. Statistical analysis was performed by Mann-Whitney test, complemented by Kruskal Wallis test (p<0.05). Only Endofill presented cytotoxicity after 24 h. MTA Fillapex and Endofill reduced the production of succinic desidrogenase after 48 h. AH Plus was non-toxic at any time point. SEM showed that the AH Plus and MTA Fillapex groups presented fibroblasts with morphology close to the control group, while the Endofill group presented few cells with thin extensions cells. The present study showed that good results were present in AH Plus and Sealapex, but not the Endofill group after 48 h. The method used enabled evaluation of the cytotoxicity of the studied sealers that diffused through the root apex.
Keywords: Cytotoxicity; Endodontics; Root canal filling